Internalisasi Konsep Ahlussunnah Wal Jamaah An-Nahdliyah Dalam Penelitian Dosen Prodi Hukum Keluarga Islam - Nu'man, Moh; Kasanah, Siti Uswatun; Arifin, Moh; Rohman, Taufiqur (SINDA: Comprehensive Journal of Islamic Social Studies, 2024)
The aim of this research is to identify and analyze the concepts and structure of the Aswaja An-Nahdliyah internalization model that are relevant to research for Islamic Family Law Study Program lecturers. using a qualitative approach with the Literature Study method, by conducting an in-depth study of the literature to examine the concepts of Aswaja An-Nahdliyah from various text sources and Nahdlatul Ulama documents for Islamic Family Law Study Program lecturers in order to deepen understanding and skills in integrating this concept. The internalization of the Aswaja concept in the research of Islamic Family Law (HKI) Study Program lecturers includes the application of the values ​​of tolerance, balance and moderation in every stage of the research. This not only has an impact on research methodology and processes, but also on the presentation and acceptance of research results in society. By implementing Aswaja principles, lecturers can produce research that is not only academically sound, but also relevant, inclusive and beneficial to the wider community.